HUSTLE CULTURE AMONG GEN Z UNIVERSITY STUDENT: BETWEEN AMBITION AND BURNOUT - Amanda Safitri; Siti Rahmatia; Narindra Diah; Triana Nur Aini (P3I UMSurabaya, 2025)
Hustle culture has become a defining characteristic among Generation Z university students who highly value continuous productivity and achievement. This culture often leads to psychological pressure and academic burnout. This study systematically reviews the relationship between hustle culture and burnout among university students following the PRISMA guidelines. Relevant articles published between 2018 and 2025 were retrieved from Google Scholar, ScienceDirect, and PsycINFO. Out of 85 initial studies, 15 met the inclusion criteria. The findings indicate a positive relationship between hustle culture and academic burnout, mediated by perfectionism, social pressure, and extrinsic motivation. Meanwhile, self-compassion and social support were found to mitigate the negative impacts. These results highlight the importance of promoting balance between ambition and psychological well-being in developing resilient Generation Z learners.